Coordinating Management disciplines to write the Philosophical, Logical and Theoretical Paradigms in Postgraduate Research - Manasseh, Tumuhimbise; Daniel, Mujuni (Humanities and Social Sciences Research, 2018)
Research is one of core requirement at postgraduate level whose immediate key output is a dissertation/thesis. This condition in postgraduate training is intended to providethe learner with a skills-set and knowledge to independently carry-on and conduct research projects for informed decision making at operational and/or strategic levels.Likewise, completion of the research projectdemonstrates the candidate’scompetence toassembling empirical evidence, use of logic to form conceptual connection between evidence and explanation. Where the research area is around general management and business situation, results are expected to provide answers, explanations, make comparisonsand arrive at generalizations which can be used to extend theory. This article contributes towards improving the postgraduate (young) researcher’s understandingthe purposeof research philosophy, logic and theorization; in conceptualization,assembling empirical evidence, discussion of results and conclusion in general management and business research.
Keywords: Research Philosophy; Research Logic; Research Theory; Deductive and Inductive approaches